2020
DOI: 10.1111/jfbc.13480
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermented Huyou juice on intestinal microbiota in a high‐fat diet‐induced obesity mouse model

Abstract: The phenomenon of obesity has been rising worldwide in the past 50 years, even reaching a pandemic level. The main reason is considered to be high energy and low nutrition diet and exercise reduction (Mazon, de Mello, Ferreira, & Rezin, 2017). Obesity represents a major health challenge because it substantially increases the incidence rates of lots of chronic diseases, such as type 2 diabetes, fatty liver disease, hypertension, asthma, and several cancers (Shan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Beta-alanine is a popular dietary supplement for competitive athletes and is associated with improved motor homeostasis and reduced neuromuscular fatigue [ 40 , 41 ]. Fermented Huyou juice can alleviate obesity by regulating several pathways, including ABC transporters [ 42 ]. However, the specific functions of these pathways in asparagus require further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Beta-alanine is a popular dietary supplement for competitive athletes and is associated with improved motor homeostasis and reduced neuromuscular fatigue [ 40 , 41 ]. Fermented Huyou juice can alleviate obesity by regulating several pathways, including ABC transporters [ 42 ]. However, the specific functions of these pathways in asparagus require further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The complex microbial community constitutes the dynamic environment of the mammalian gastrointestinal tract. HFD has a significant impact on the gut microbiota, which can induce obesity and obesityrelated complications (Yan et al, 2020). Meanwhile, the gut microbiota, similar to environmental factors, could play a role in regulating the storage and metabolism of fat (Backhed et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fermented fruit products also could improve intestinal microbiota via increasing the abundance of beneficial bacteria and inhibiting the growth of harmful bacteria. A study has indicated that administration with fermented fruit increased the abundance of beneficial bacteria including Bacteroides , Roseburia , Butyrivibrio , Lactobacillus , and Akkermansia , thus, relieving obesity and hyperlipidemia ( Yan, Wang, Weng, & Wu, 2020 ). While improving the structure of intestinal microbiota, the intestinal micro-environment will be also improved via increasing the levels of short-chain fatty acid and enhancing intestinal immunity ( Valero-Cases, Cerda-Bernad, Pastor, & Frutos, 2020 ).…”
Section: The Beneficial Effect Of Fruit Fermentationmentioning
confidence: 99%